Introduction to nutrition and metabolism. - Bender, David A., 1946- (Boca Raton : CRC, 2008)
This fourth edition of a bestseller has been thoroughly updated and provides a clear introduction to the basic science of nutrition and metabolism. It explains the scientific principles underlying our current understanding of the interactions between diet and health; explores the scientific basis of dietary goals and recommendations; and provides an authoritative description of the basics of biochemistry. New features include a list of key points at the end of each chapter and the addition of open-ended case-based problems. The accompanying CD-ROM has been revised to include PowerPoint presentations, self-assessment exercises, simulations of laboratory experiments, and a nutrient analysis program.
Keywords: Voeding